A whole-system approach to high-performance green buildings - Strong, David, 1953-; Burrows, Victoria, 1985- (Artech House integrated microsystems series., 2017)
This book provides a comprehensive review of the current approaches to the design and construction of sustainable buildings. This hand-on guide features global case studies with practical examples of both successful and unsuccessful designs.